Selective bisubstrate inhibitors with sub-nanomolar affinity for protein kinase Pim-1. - Ekambaram, R; Enkvist, E; Vaasa, A; Kasari, M; Raidaru, G; Knapp, S; Uri, A (2013)
Potent and selective: The unique nature of the ATP binding pocket structure of Pim family protein kinases (PKs) was used for the development of bisubstrate inhibitors and a fluorescent probe with sub-nanomolar affinity. Conjugates of arginine-rich peptides with two ATP mimetic scaffolds were synthesized and tested as inhibitors of Pim-1. Against a panel of 124 protein kinases, a novel ARC-PIM conjugate selectively inhibited PKs of the Pim family.